PERBANDINGAN ANALISIS TEKNIKAL CLASSIC DAN COMPUTERIZED INVESTASI FOREX ONLINE PADA PASANGAN MATA UANG GBP/USD - Glavenia Wiranata; Dewi Ratih (Universitas Katolik Widya Karya Malang, 2020)
Online forex traders who prioritize technical analysis will dealwith two options, namely technical analysis of classic andcomputerized technical analysis where each technique ofanalysis is using different ways.Through research with the aim to know the comparison oftrading positions using technical analysis classic andcomputerized on GBP/USD currency pair can be knownclearly the advantages and disadvantages of each technique.From the results of this study traders can more easily choosethe method or technique what will be used in the process ofmaking investment decisions.The type of research is descriptive research by depicting andanalyzing graph data of price movement of GBP/USD currencypair. Data retrieval in this research is to observe directly chartof forex price movement during period April 2012 - April 2015from Platform Meta Trader 4.The results showed that there were eleven open positionsconsisting of six buy positions and five sell positions usingtechnical classic analysis which resulted in total pips of5,373.8 pips and there were six open positions consisting ofthree buy positions and three sell positions usingcomputerized technical analysis which produces a total pip of3,165.9 pips. Classical technical analysis techniques are moreprofitable because they generate greater profits than usingcomputerized analysis (profit margin of 2,207.9 pips).